Boundary-element parallel-computing algorithm for the microstructural analysis of general composites - Araújo, F.C.; d’Azevedo, E.F.; Gray, L.J. (Computers & structures, 2010)
A standard continuum-mechanics-based 3D boundary-element (BE) algorithm has been devised to the microstructural modeling of complex heterogeneous solids such as general composites. In the particular applications of this paper, the mechanical properties of carbon-nanotube–reinforced composites are estimated from three-dimensional representative volume elements (RVEs). The shell-like thin-walled carbon nanotubes (CNTs) are also simulated with 3D BE models, and a generic subregion-by-subregion (SBS) algorithm makes the microstructural description of the CNT–polymer systems possible. In fact, based on this algorithm, a general scalable BE parallel code is proposed. Square and hexagonal fiber-packing patterns are considered to simulate the 3D composite microstructures.